Psychological Welfare on Organizational Commitment in Insurance Agents through Turnover Intention - Ilhammuddin Ilhammuddin; I Made Adnyana (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to examine and analyze the effect of job satisfaction and mental health on welfare partially and to formulate company policies related to agent turnover intention for company progress. The research used Analysis of Moment Structure-Structural Equation Modeling (AMOS-SEM) using 150 samples. The research findings show that job withdrawal, as opposed to job satisfaction and mental health, has a direct, beneficial, and large effect on intention to leave. In addition, well-being has a direct, significant, and beneficial effect on intentions to migrate. Meanwhile, the effect of work engagement on organizational commitment is negligible and direct. Meanwhile, Job Satisfaction has a negative and insignificant direct impact on well-being, a large psychological impact on organizational commitment.